Manufacturing method of dielectric sheet, manufacturing method of substrate for high frequency printed wiring board, dielectric sheet, and substrate for high frequency printed wiring board

The extrusion and rolling process with controlled silica-polytetrafluoroethylene ratios and particle sizes addresses the challenges of uniformity and stability in dielectric sheet manufacturing, resulting in high-frequency printed wiring boards with improved characteristics and durability.

JP7608450B2Active Publication Date: 2025-01-06SUMITOMO ELECTRIC INDUSTRIES LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2022524401
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-05-18
Filing Date
2021-05-11
Publication Date
2025-01-06
Estimated Expiration
2041-05-11

Smart Images

  • Figure 0007608450000002
    Figure 0007608450000002
  • Figure 0007608450000003
    Figure 0007608450000003
  • Figure 0007608450000004
    Figure 0007608450000004
Patent Text Reader

Abstract

A method for manufacturing a dielectric sheet comprises a step for extruding a mixture including polytetrafluoroethylene in powder form and spherical silica at the melting point of the polytetrafluoroethylene or lower, and a step for rolling a sheet body obtained by the extruding step. The mass ratio of the silica to the polytetrafluoroethylene is at least 1.3. The mean particle size of the silica is 0.1-3.0 μm. The reduction ratio in the extruding step is at most 8.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a method for producing a dielectric sheet, a method for producing a substrate for a high-frequency printed wiring board, a dielectric sheet, and a substrate for a high-frequency printed wiring board.

[0002] This application claims priority to Japanese Application No. 2020-087052, filed on May 18, 2020, and incorporates by reference all of the contents of said Japanese application. [Background technology]

[0003] In recent years, with the trend toward smaller and lighter electronic devices, there is an increasing demand for smaller printed wiring boards used in these electronic devices. For this reason, polyimide films, which have excellent insulation properties, flexibility, heat resistance, etc. and can be made thinner, are now being used as base films for printed wiring boards (see Patent Document 1).

[0004] On the other hand, the amount of information being transmitted is constantly increasing, and in order to meet this demand, communication in high frequency ranges such as microwaves and millimeter waves is becoming more common in devices such as IC cards and mobile communication terminals. For this reason, there is a demand for high frequency printed wiring boards with low transmission loss when used in high frequency ranges. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Patent Application Publication No. 2008-235346 Summary of the Invention

[0006] The manufacturing method of the dielectric sheet of the present disclosure includes a step of extruding a mixture containing powdered polytetrafluoroethylene and spherical silica at a temperature below the melting point of the polytetrafluoroethylene, and a step of rolling a sheet body obtained by the extrusion molding step, wherein the mass ratio of the silica to the polytetrafluoroethylene is 1.3 or more, the average particle size of the silica is 0.1 μm or more and 3.0 μm or less, and the reduction ratio in the extrusion molding is 8 or less.

[0007] Another method for manufacturing a dielectric sheet according to the present disclosure includes the steps of extruding a mixture containing powdered polytetrafluoroethylene and spherical silica at or below the melting point of the polytetrafluoroethylene, and rolling a sheet body obtained by the extrusion molding, wherein the mass ratio of the silica to the polytetrafluoroethylene is 1.3 or more, the silica includes a first silica having an average particle size of 0.1 μm or more and 0.9 μm or less and a second silica having an average particle size of 4.0 μm or more and 9.0 μm or less, the mass ratio of the first silica to the polytetrafluoroethylene is 0.2 or more and 1.9 or less, and a reduction ratio in the extrusion molding is 8 or less.

[0008] The dielectric sheet of the present disclosure contains silica and polytetrafluoroethylene, wherein the mass ratio of the silica to the polytetrafluoroethylene is 1.3 or more, the ratio of maximum tensile elongation to minimum tensile elongation is 1.5 or less, and the minimum tensile elongation is 40% or more. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a schematic cross-sectional view of a dielectric sheet according to an embodiment of the present disclosure. [Diagram 2] FIG. 2 is a vertical cross section of the dielectric sheet taken in the thickness direction using a scanning electron microscope. [Diagram 3] FIG. 3 is a schematic cross-sectional view of a substrate for high-frequency printed wiring boards according to an embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] [Problem that this disclosure aims to solve] Base films mainly composed of fluororesin are known as insulating substrates for printed wiring boards. Because fluororesin has a low dielectric constant, base films mainly composed of fluororesin are suitable as insulating substrates for printed wiring boards used for high-frequency signal processing. Films made of such fluororesin alone can be easily obtained with little variation in thickness and material composition by extruding them into a tape shape by extrusion molding and rolling them into a thin sheet.

[0011] In order to ensure good high-frequency characteristics of the printed wiring board, the insulating substrate of the printed wiring board is required to have small dimensional changes with temperature changes and small variations in thickness and composition, but fluororesin does not have sufficient dimensional stability with respect to temperature changes. In response to this, by blending a filler into the base film, the dimensional stability of the base film with respect to temperature changes can be improved. However, if a large amount of filler is blended into a base film mainly composed of fluororesin, it becomes difficult to perform extrusion molding and rolling with general-purpose equipment and manufacturing conditions, such as requiring extremely high molding pressure. Therefore, in the manufacture of base films, manufacturing methods other than extrusion molding and rolling are generally adopted. For example, there is a manufacturing method in which a mixture of polytetrafluoroethylene and inorganic filler is compressed at high pressure and at a high temperature above the melting point of polytetrafluoroethylene, and then scraped into a sheet shape. This method has a large variation in thickness and requires very large-scale equipment. In addition, there is a manufacturing method in which a mixture of polytetrafluoroethylene and inorganic filler is dispersed in a liquid to form a low-viscosity slurry, which is applied to a carrier film and dried to solidify. This method has a problem that the inorganic filler is precipitated, resulting in different distributions of the inorganic filler on the surface that contacts the carrier film and the surface that does not contact the carrier film. These methods may be inferior to the "process of rolling an extrusion-molded sheet" in terms of cost, thickness variation, filler dispersibility, etc.

[0012] The present disclosure has been made in light of the above-mentioned circumstances, and has an object to provide a method for producing a dielectric sheet that can produce a dielectric sheet having excellent high-frequency characteristics using extrusion molding and rolling.

[0013] [Effects of this disclosure] The method for producing a dielectric sheet according to the present disclosure can easily and reliably produce a dielectric sheet having excellent high-frequency characteristics.

[0014] [Description of the embodiments of the present disclosure] First, the embodiments of the present disclosure will be listed and described.

[0015] A method for manufacturing a dielectric sheet according to one embodiment of the present disclosure includes the steps of extruding a mixture containing powdered polytetrafluoroethylene and spherical silica at a temperature below the melting point of the polytetrafluoroethylene, and rolling a sheet body obtained by the extrusion molding, wherein the mass ratio of the silica to the polytetrafluoroethylene is 1.3 or more, the average particle size of the silica is 0.1 μm or more and 3.0 μm or less, and a reduction ratio in the extrusion molding is 8 or less.

[0016] The dielectric sheet manufacturing method can reliably manufacture a dielectric sheet with excellent high-frequency characteristics. The reasons for this are considered to be as follows. As described above, fluororesins such as polytetrafluoroethylene have a low dielectric constant and a low dielectric loss tangent, so that the high-frequency characteristics of a high-frequency printed wiring board manufactured from a substrate using fluororesin are good, but the linear expansion coefficient with respect to temperature change is large and the dimensional stability is insufficient. At high frequencies, the wavelength becomes shorter, so that the effect of dimensional changes in the circuit on the electrical characteristics of the circuit becomes greater. Therefore, this large linear expansion coefficient may deteriorate the high-frequency characteristics of the circuit. In the dielectric sheet manufacturing method, the mass ratio of silica to polytetrafluoroethylene is 1.3 or more, so that the linear expansion coefficient of the dielectric sheet can be reduced, and the dimensional stability of the base film against temperature changes can be improved.

[0017] When a large amount of filler is blended into the resin composition, an extremely large extrusion molding pressure is required. In addition, blending of the filler reduces the cohesive force. When the cohesive force is reduced, the ends of the flow path in the extrusion molding are easily affected by frictional forces with the inner wall of the extruder, and the extrusion pressure is less applied to the ends than to the center, so that cracks are generated between the ends and the center, and only the center is extruded, or even if cracks do not occur, the extrusion speed of the center is faster than that of the ends, so that wrinkles tend to occur in the center. Furthermore, in the extrusion molding using polytetrafluoroethylene, fiberization, that is, molecular chains are elongated and oriented in the longitudinal direction, which increases the extrusion molding pressure, and cracks tend to occur due to the low cohesive force between the oriented fibers. Therefore, it is extremely difficult to perform stable and uniform extrusion molding. The manufacturing method of the dielectric sheet employs extrusion molding and rolling with good production efficiency, and by setting the reduction ratio (RR: Reduction Ratio) in the extrusion molding to 8 or less, excessive increase in strength in the longitudinal direction due to the molecular chains of polytetrafluoroethylene being oriented in the longitudinal direction is suppressed. Therefore, the frictional force between the inner wall of the extruder and the mixture can be reduced, and extrusion molding can be performed at a low pressure.

[0018] In addition, it has been generally known that in the extrusion molding of a resin composition, the smaller the particle size of the filler to be blended, the larger the contact area between the filler and the resin composition, resulting in a higher molding viscosity, which requires a high extrusion molding pressure and makes the extrusion molding difficult. In contrast, the present inventors have found that when a filler is blended with polytetrafluoroethylene, the smaller the particle size of the silica, the lower the pressure at which the extrusion molding can be performed. This is thought to be because the silica covers the surface of the polytetrafluoroethylene particles, preventing fibrosis caused by contact between the polytetrafluoroethylene particles, thereby making it possible to extrude at a low pressure. In the manufacturing method of the dielectric sheet, the average particle size of the silica is 0.1 μm or more and 3.0 μm or less, making it possible to extrude at a low pressure, and without generating cracks or wrinkles, it is possible to easily and reliably manufacture a dielectric sheet that is excellent in high frequency characteristics by ensuring the uniformity of the filler and the uniformity of the thickness as a thin film.

[0019] In addition, a manufacturing method of a dielectric sheet according to another embodiment of the present disclosure includes a step of extruding a mixture containing powdered polytetrafluoroethylene and spherical silica at or below the melting point of the polytetrafluoroethylene, and a step of rolling a sheet body obtained by the extrusion molding step, wherein the mass ratio of the silica to the polytetrafluoroethylene is 1.3 or more, the silica includes a first silica having an average particle size of 0.1 μm or more and 0.9 μm or less and a second silica having an average particle size of 4.0 μm or more and 9.0 μm or less, the mass ratio of the first silica to the polytetrafluoroethylene is 0.2 or more and 1.9 or less, and a reduction ratio in the extrusion molding is 8 or less.

[0020] The dielectric sheet manufacturing method can reliably manufacture a dielectric sheet with excellent high-frequency characteristics. The reasons for this are considered to be as follows. As described above, fluororesins such as polytetrafluoroethylene have a low dielectric constant and a low dielectric loss tangent, so that the high-frequency characteristics of a high-frequency printed wiring board manufactured from a substrate using fluororesin are good, but the linear expansion coefficient with respect to temperature change is large and the dimensional stability is insufficient. At high frequencies, the wavelength becomes shorter, so that the effect of dimensional changes in the circuit on the electrical characteristics of the circuit becomes greater. Therefore, this large linear expansion coefficient may deteriorate the high-frequency characteristics of the circuit. In the dielectric sheet manufacturing method, the mass ratio of silica to polytetrafluoroethylene is 1.3 or more, so that the linear expansion coefficient of the dielectric sheet can be reduced, and the dimensional stability of the base film against temperature changes can be improved.

[0021] When a large amount of filler is blended into the resin composition, an extremely large extrusion molding pressure is required. In addition, blending of the filler reduces the cohesive force. When the cohesive force is reduced, the ends of the flow path in the extrusion molding are easily affected by frictional forces with the inner wall of the extruder, and the extrusion pressure is less applied to the ends than to the center, so that cracks are generated between the ends and the center, and only the center is extruded, or even if cracks do not occur, the extrusion speed of the center is faster than that of the ends, so that wrinkles tend to occur in the center. Furthermore, in the extrusion molding using polytetrafluoroethylene, fiberization, that is, molecular chains are elongated and oriented in the longitudinal direction, which increases the extrusion molding pressure, and cracks tend to occur due to the low cohesive force between the oriented fibers. Therefore, it is extremely difficult to perform stable and uniform extrusion molding. The manufacturing method of the dielectric sheet employs extrusion molding and rolling with good production efficiency, and by setting the reduction ratio (RR: Reduction Ratio) in the extrusion molding to 8 or less, excessive increase in strength in the longitudinal direction due to the molecular chains of polytetrafluoroethylene being oriented in the longitudinal direction is suppressed. Therefore, the frictional force between the inner wall of the extruder and the mixture can be reduced, and extrusion molding can be performed at a low pressure.

[0022] In addition, it has been generally known that in extrusion molding of a resin composition, the smaller the particle size of the filler to be mixed, the larger the contact area between the filler and the resin composition, resulting in a higher molding viscosity, which requires a high extrusion molding pressure and makes extrusion molding difficult. In the manufacturing method of the dielectric sheet, the silica includes a combination of a first silica having an average particle size of 0.1 μm to 0.9 μm and a second silica having an average particle size of 4.0 μm to 9.0 μm, and the mass ratio of the first silica to the polytetrafluoroethylene is within the above range, making it possible to perform extrusion molding at a low pressure, ensuring the uniformity of the filler and the uniformity of the thickness as a thin film without causing cracks or wrinkles, and easily and reliably manufacturing a dielectric sheet with excellent high-frequency characteristics.

[0023] The rolling reduction in the rolling step is preferably 0.93 or more. In this way, by having the rolling reduction of 0.93 or more, the fiberization of polytetrafluoroethylene is promoted in the rolling step to increase elongation, thereby obtaining a dielectric sheet with good folding resistance. In addition, since there is no need to promote the fiberization of polytetrafluoroethylene, which requires high pressure in extrusion molding, extrusion molding at low pressure is possible.

[0024] A method for manufacturing a high-frequency printed wiring board substrate according to another embodiment of the present disclosure includes a step of laminating copper foil directly or indirectly on the surface of a dielectric sheet manufactured by the method for manufacturing the dielectric sheet. The step of indirectly laminating copper foil on the surface of a dielectric sheet is, for example, a step of laminating copper foil on the surface of a dielectric sheet after performing a surface treatment of the dielectric sheet, or a step of laminating copper foil on the surface of a dielectric sheet via another layer. In the method for manufacturing a high-frequency printed wiring board substrate, the mass ratio of silica to polytetrafluoroethylene is 1.3 or more, so that the linear expansion coefficient of the dielectric sheet can be reduced, and the dimensional stability of the base film against temperature changes can be improved. In addition, by setting the reduction ratio in the extrusion molding to 8 or less, the friction force between the inner wall of the extruder and the mixture can be reduced, and extrusion molding can be performed at a low pressure. The method for manufacturing a high-frequency printed wiring board substrate includes a step of laminating copper foil directly or indirectly on the surface of a dielectric sheet having excellent high-frequency characteristics, so that a high-frequency printed wiring board substrate having excellent high-frequency characteristics can be easily and reliably manufactured.

[0025] In the manufacturing method of the high frequency printed wiring board substrate, in the step of laminating the copper foil, the copper foil is laminated on the surface of the dielectric sheet via an adhesive layer, and the adhesive layer preferably contains a thermoplastic fluororesin as a main component. In the step of laminating the copper foil, the copper foil is laminated on the surface of the dielectric sheet via an adhesive layer, and the adhesive layer preferably contains a thermoplastic fluororesin as a main component, so that the low roughness copper foil and the dielectric sheet can be firmly bonded while maintaining good high frequency characteristics due to the fluororesin.

[0026] A dielectric sheet according to another embodiment of the present disclosure contains silica and polytetrafluoroethylene, wherein the mass ratio of the silica to the polytetrafluoroethylene is 1.3 or more, the maximum tensile elongation relative to the minimum tensile elongation is 1.5 or less, and the minimum tensile elongation is 40% or more.

[0027] The dielectric sheet contains polytetrafluoroethylene, and therefore has excellent high frequency characteristics. In addition, since the mass ratio of silica to polytetrafluoroethylene is 1.3 or more, the linear expansion coefficient of the dielectric sheet can be reduced, and the dimensional stability of the dielectric sheet against temperature changes can be improved. Therefore, the dielectric sheet has excellent high frequency characteristics. In addition, when the mass ratio of silica is high, the characteristics of the dielectric sheet approach those of ceramics, and therefore usually have low elongation and low folding resistance. However, the dielectric sheet has a maximum tensile elongation rate relative to the minimum tensile elongation rate (hereinafter also referred to as anisotropic coefficient of elongation) of 1.5 or less, and the minimum tensile elongation rate is 40% or more, and therefore has excellent folding resistance despite the high mass ratio of silica.

[0028] The dielectric sheet preferably has, in a longitudinal section in the thickness direction, a layered first phase mainly composed of polytetrafluoroethylene and a layered second phase mainly composed of silica. The dielectric sheet having the first and second phases can more easily exhibit the properties of polytetrafluoroethylene, namely high elongation and high strength due to fiberization, and the property of silica, namely a reduced linear expansion coefficient.

[0029] In the dielectric sheet, the thickness of the first phase is preferably 0.1 μm or more and 10.0 μm or less. If the thickness of the layered first phase is less than the lower limit, the degree of fiberization of polytetrafluoroethylene may decrease, making it difficult to obtain the characteristic of high elongation. On the other hand, if the thickness of the first phase exceeds the upper limit, it may be difficult to reduce the linear expansion coefficient to a desired range.

[0030] It is preferable that the silica has, on its surface, an alkyl group having 4 or more carbon atoms. When the silica has, on its surface, an alkyl group having 4 or more carbon atoms, the adhesion between the silica and the polytetrafluoroethylene increases, improving elongation, and the dielectric sheet has excellent folding resistance.

[0031] A substrate for a high-frequency printed wiring board according to another embodiment of the present disclosure includes the dielectric sheet and a copper foil directly or indirectly laminated on a surface of the dielectric sheet.

[0032] The substrate for high-frequency printed wiring boards comprises the dielectric sheet and copper foil laminated directly or indirectly on the surface of the dielectric sheet, and therefore the substrate for high-frequency printed wiring boards has excellent high-frequency characteristics and folding resistance.

[0033] It is preferable that the maximum height roughness Rz of the surface of the copper foil on the dielectric sheet side is 2 μm or less. In this way, by having the maximum height roughness Rz of the surface on the dielectric sheet side within the above range, the unevenness of the portion where the high frequency signal is concentrated due to the skin effect is reduced, and the current is more likely to flow linearly, so that the transmission loss can be further suppressed. Therefore, the high frequency characteristics of the substrate for high frequency printed wiring boards can be further improved.

[0034] It is preferable that the copper foil is laminated on the surface of the dielectric sheet via an adhesive layer mainly made of fluororesin. By laminating the copper foil on the surface of the dielectric sheet via an adhesive layer mainly made of fluororesin, the low-roughness copper foil and the dielectric sheet can be firmly bonded while maintaining good high-frequency characteristics due to the fluororesin.

[0035] In this disclosure, the "average particle size" of the silica refers to the particle size of the primary particles, which is expressed by the median diameter D50 of the volume particle size distribution. The average particle size can be measured by a particle size distribution measuring device (for example, "MT3300II" by Microtrack Bell Co., Ltd.). "Reduction ratio" refers to the maximum cross-sectional area divided by the minimum cross-sectional area of ​​the cross-sectional area of ​​the flow path through which the extrusion molded product passes in the extrusion molding process. "Maximum height roughness Rz" refers to the maximum height roughness measured in accordance with JIS-B-0601 (1982). "Main component" refers to the component with the highest content, for example, a component with a content of 50 mass% or more. "Rolling reduction ratio" refers to the rate of change in sheet thickness expressed as (h0-h1) / h0, where h0 is the thickness of the sheet before the rolling process and h1 is the thickness of the sheet after the rolling process (the final stage when rolling is performed in two or more stages). A larger reduction ratio indicates a larger change in thickness of the sheet due to the rolling process. "Maximum tensile elongation" refers to the maximum tensile elongation in all in-plane directions of the dielectric sheet measured by a test method conforming to IPC-TM-650 2.4.19, and "minimum tensile elongation" refers to the minimum tensile elongation measured in the same manner.

[0036] [Details of the embodiment of the present disclosure] Hereinafter, a method for producing a dielectric sheet, a method for producing a substrate for a high-frequency printed wiring board, a dielectric sheet, and a substrate for a high-frequency printed wiring board according to embodiments of the present disclosure will be described in detail.

[0037] <Method of manufacturing dielectric sheet> The method for producing a dielectric sheet includes the steps of preparing powdered polytetrafluoroethylene and spherical silica, extruding a mixture containing the powdered polytetrafluoroethylene and the spherical silica at a temperature equal to or lower than the melting point of the polytetrafluoroethylene, and rolling a sheet body obtained by the extrusion molding step. The method for producing a dielectric sheet employs the extrusion molding step and the rolling step, thereby making it possible to efficiently produce a dielectric sheet containing polytetrafluoroethylene. The method for producing a dielectric sheet preferably further includes a step of mixing materials and a step of removing an auxiliary agent.

[0038] [Process of mixing materials] In this process, powdered polytetrafluoroethylene and spherical silica are prepared, and a mixture containing the powdered polytetrafluoroethylene and the spherical silica is manufactured. In addition, it is preferable to add an auxiliary agent (liquid lubricant) to the mixture. Hereinafter, the powdered polytetrafluoroethylene may be referred to as "polytetrafluoroethylene powder", and the spherical silica may be simply referred to as "silica".

[0039] The mixing method is not particularly limited as long as it can mix the materials. The mixing method includes a dry method, i.e., a method of mixing polytetrafluoroethylene powder, silica powder, and an auxiliary, and a wet method, i.e., a method of mixing a polytetrafluoroethylene dispersion with a liquid in which silica is dispersed, coagulating and recovering the mixture, and mixing the auxiliary. The dry method is preferred because it is easy to obtain a state in which the first and second phases are in a layered form. In the dry method, for example, the polytetrafluoroethylene powder, silica, and auxiliary are placed in a sealed container, and the container is rotated at a low temperature of 10°C or less to mix the materials.

[0040] The polytetrafluoroethylene powder is not particularly limited as long as it is used in extrusion molding, but fine powder can be preferably used. Fine powder is a powder obtained by coagulating and drying a dispersion of polytetrafluoroethylene having an average particle size of 0.1 to 0.5 μm obtained by emulsion polymerization of tetrafluoroethylene. The average particle size of the powder is, for example, 20 μm to 1000 μm. Since a uniform fine dispersion state with silica can be easily formed, the upper limit of the average particle size of the polytetrafluoroethylene powder is preferably 700 μm, more preferably 500 μm, and even more preferably 400 μm. In terms of being able to moderately proceed with the fiberization of polytetrafluoroethylene, the lower limit of the average particle size of the powder is preferably 50 μm, more preferably 100 μm, and even more preferably 200 μm.

[0041] The silica may be natural or synthetic, crystalline or amorphous, and may be produced by a dry process or a wet process, but from the viewpoint of availability and quality, synthetic silica produced by a dry process is preferred. It is preferable that the silica is spherical because of its good processability such as drilling. In a general silica production method, silica has one peak in its particle size distribution, and the distribution gradually decreases around the peak. As a result of cutting particles with a particle size of a certain size or more, the particle size distribution has a distribution with the large particle size side cut off, and as a result, many silicas with a smaller average particle size than those without the cut are commercially available. From the viewpoint of processability such as drilling, the upper limit of the average particle size of the silica is preferably 9.0 μm, more preferably 7.0 μm, even more preferably 5.0 μm, and particularly preferably 3.0 μm or less.

[0042] In the extrusion molding of a mixture of silica and polytetrafluoroethylene, the polytetrafluoroethylene becomes fibrous, that is, the molecular chains are elongated and oriented in the longitudinal direction, and the extrusion molding pressure becomes higher than in the case of polytetrafluoroethylene alone. In normal extrusion molding, the smaller the particle size of silica, the higher the viscosity of the extrusion molding product becomes, and the higher pressure is required. However, according to the findings of the present inventors, in the mixture of polytetrafluoroethylene and silica, if the particle size is appropriately small, fibrous formation does not progress easily, and the molding pressure can be suppressed. In the extrusion molding process, fibrous formation occurs at the contact point between adjacent polytetrafluoroethylene powders. When polytetrafluoroethylene and moderately small silica are mixed in the mixing process, it is considered that the silica with a small particle size covers the surface layer of polytetrafluoroethylene, suppressing the contact between polytetrafluoroethylene particles in the subsequent extrusion molding process, and thus suppressing the fibrous formation, thereby suppressing the extrusion molding pressure.

[0043] Since extrusion molding can be performed at low pressure, the average particle size of the silica is preferably 3.0 μm or less, more preferably 2.0 μm or less, and even more preferably 1.0 μm or less. By having the average particle size of the silica in the above range, the uniformity of the filler and the uniformity of the thickness as a thin film can be ensured without cracks or wrinkles, and a dielectric sheet with excellent high-frequency characteristics can be easily and reliably manufactured. In addition, it is preferably 0.1 μm or more, preferably 0.3 μm or more, and even more preferably 0.5 μm or more. Silica with an average particle size smaller than 0.1 μm can be manufactured by the sol-gel method, but it is prone to aggregation and difficult to disperse. Even if dispersed, the surface area becomes large, so the action of silica and polytetrafluoroethylene greatly affects the physical properties, and there is a risk of increasing the extrusion molding pressure or decreasing the elongation of the molded product. Note that multiple silicas with different average particle sizes in the above range may be used in combination.

[0044] In addition, when using silica with an average particle size larger than 3.0 μm, it is possible to perform extrusion molding at low pressure by combining it with silica with an appropriately small diameter. Specifically, it is preferable to mix large-diameter silica with an average particle size of 4.0 μm to 9.0 μm and small-diameter silica with an average particle size of 0.1 μm to 0.9 μm. The average particle size of the large-diameter silica is more preferably 5.0 μm to 8.0 μm, and even more preferably 6.0 μm to 7.0 μm. The average particle size of the small-diameter silica is more preferably 0.1 μm to 0.7 μm, and even more preferably 0.1 μm to 0.4 μm. By covering the surface layer of polytetrafluoroethylene with small-diameter silica, it is possible to suppress the fibrous formation of polytetrafluoroethylene and to perform extrusion molding at low pressure. Furthermore, by mixing with large-diameter silica, it is possible to easily express the characteristics due to polytetrafluoroethylene, such as high elongation and high cohesive force, compared to the case of only small-diameter silica, and to reduce the linear expansion coefficient. When small-diameter silica and large-diameter silica are blended, the mass ratio of small-diameter silica to polytetrafluoroethylene is preferably 0.2 to 1.9, more preferably 0.2 to 1.5, even more preferably 0.3 to 1.0, and particularly preferably 0.4 to 0.7.

[0045] It is preferable that the silica has an alkyl group having 4 or more carbon atoms on the surface. When the silica has an alkyl group having 4 or more carbon atoms on the surface, the adhesion between the silica and polytetrafluoroethylene is increased and the elongation is improved, so that a dielectric sheet having excellent folding resistance can be manufactured. From the viewpoint of the bonding between the surface of the silica and the alkyl group, the number of carbon atoms is more preferably 5 or more so that an interaction with polytetrafluoroethylene occurs easily. On the other hand, the upper limit of the number of carbon atoms is preferably 10 or less. In addition, the alkyl group is preferably a linear alkyl. Examples of the alkyl group having 4 or more carbon atoms include a butyl group, a pentyl group, a hexyl group, a heptyl group, an octyl group, a nonyl group, and a decyl group.

[0046] It is preferable that the silica does not contain functional groups other than alkyl groups, i.e., vinyl groups, epoxy groups, styryl groups, methacryl groups, acrylic groups, amino groups, isocyanate groups, phenyl groups, isocyanurate groups, etc., on the surface. It has been reported that the mechanical strength is improved as a result of reducing the amount of water absorbed by treating the surface of silica to be hydrophobic, but the improvement in elongation due to the presence of an alkyl group having 4 or more carbon atoms is mainly due to the bonding effect between polytetrafluoroethylene and silica, not due to an increase in hydrophobicity. When the dielectric sheet is stretched and the cross section of the torn piece is observed, it can be confirmed that the ends of the stretched polytetrafluoroethylene fibers are firmly bonded to the silica surface, and fiberization occurs from there. For example, even if silica having a vinyl group on the surface, which has a higher degree of hydrophobicity, is used, such a bonding effect is small, and therefore the effect of improving elongation is small.

[0047] The lower limit of the mass ratio of silica to polytetrafluoroethylene is 1.3, preferably 1.5, and more preferably 1.6. Meanwhile, the upper limit of the mass ratio of silica is preferably 2.0, and more preferably 1.9. By making the mass ratio of silica to polytetrafluoroethylene 1.3 or more, the linear expansion coefficient of the dielectric sheet can be reduced, and the dimensional stability of the dielectric sheet against temperature changes can be improved. Meanwhile, if the mass ratio of silica exceeds the upper limit, the dielectric sheet becomes brittle, and there is a risk that the handling properties and folding resistance are reduced. From the viewpoint of reducing the linear expansion coefficient, when a filler other than silica having a small linear expansion coefficient is blended, the amount of silica can be reduced.

[0048] In this blend, if necessary, inorganic fillers other than silica, such as aluminum oxide, magnesium oxide, calcium oxide, talc, barium sulfate, boron nitride, zinc oxide, potassium titanate, glass, titanium oxide, and mica, may be included within a range that does not adversely affect the desired properties. Inorganic fillers generally have a small linear expansion coefficient, so when an inorganic filler other than silica is blended, the amount of silica blended can be reduced according to the blending amount. Titanium oxide is preferably blended because it has the opposite temperature change characteristic of the dielectric constant to silica and the like, and can improve the temperature stability of the dielectric constant.

[0049] The above-mentioned auxiliary agent is not particularly limited as long as it can wet polytetrafluoroethylene, facilitate plastic deformation, and be easily removed by heating after the rolling process. For example, petroleum solvents such as solvent naphtha and white oil, hydrocarbon oils such as undecane, aromatic hydrocarbons such as toluene and xylol, alcohols, ketones, esters, silicone oil, fluorochlorocarbon oil, solutions in which polymers such as polyisobutylene and polyisoprene are dissolved in these solvents, mixtures of two or more of these, water or an aqueous solution containing a surfactant, etc. can be mentioned. A single component is preferable to a mixture because it can be mixed uniformly. The amount of the auxiliary agent is not particularly limited as long as it can wet polytetrafluoroethylene, but the mass ratio to polytetrafluoroethylene is preferably 0.1 to 0.8, more preferably 0.2 to 0.7, and even more preferably 0.3 to 0.6.

[0050] [Extrusion molding process] In this process, a mixture containing polytetrafluoroethylene powder and spherical silica is extruded at a temperature below the melting point of the polytetrafluoroethylene.

[0051] The extrusion temperature is equal to or lower than the melting point of the polytetrafluoroethylene. Specifically, the upper limit of the extrusion temperature is preferably 100°C. The extrusion temperature is preferably equal to or higher than the transition temperature of the polytetrafluoroethylene around room temperature. Specifically, the lower limit of the extrusion temperature is preferably 40°C. By setting the extrusion temperature within the above range, the extrusion can be stably performed.

[0052] The shape of the cut surface of the mixture obtained by the extrusion molding in this step on a plane perpendicular to the extrusion direction is preferably a flat shape such as a rectangle or an ellipse. This is because it is easy to put into the rolling roll in the rolling step of the next step, and the sheet after rolling is excellent in uniformity. The shape of the cut surface is particularly preferably a rectangle. For example, when the cut surface is extruded so that it has a circular shape, that is, in a cylindrical shape, it becomes difficult to bite between the upper and lower rolling rolls in the rolling step, so that rolling becomes difficult. If the molded body is forcibly pressed between the rolling rolls by applying pressure, the molded body is crushed and enters between the rolling rolls in an uneven state including voids, so that the thickness of the rolled product varies and a sheet containing voids is formed, which is not preferable. When considering the smallest rectangle that contains the flat cross section inside and contacts the outer periphery of the cross section at several points, the larger the ratio of the long side length to the short side length, the easier it is to put into the rolling roll and the sheet after rolling is excellent in uniformity, which is preferable. On the other hand, the larger the ratio of the long side length to the short side length, the less likely it is that the extrusion pressure will be transmitted to the end portion (the end portion formed by the short side and the long side end portion), and the more likely it is that the end portion will tear from the center portion to the center portion (the portion adjacent to the center of the long side), resulting in only the center portion being extruded. Therefore, the ratio of the long side length to the short side length is preferably 6 to 25, more preferably 8 to 20, and even more preferably 10 to 15.

[0053] In general, the reduction ratio used in the extrusion molding of polytetrafluoroethylene is preferably 10 or more and 1000 or less. The upper limit of the reduction ratio in this process is 8 or less, preferably 6 or less, more preferably 5 or less, and even more preferably 4 or less. By setting the upper limit of the reduction ratio in the extrusion molding process within the above range, excessive increase in strength in the longitudinal direction due to the orientation of the molecular chains of polytetrafluoroethylene in the longitudinal direction is suppressed, so that the friction force between the inner wall of the extruder and the above mixture can be reduced, and extrusion molding can be performed at low pressure without cracking or clogging of the ends. In addition, by extrusion molding at low pressure, the orientation of the polytetrafluoroethylene fibers in the extrusion molding direction can be weakened, and as a result, it is possible to expand the room for adjusting the anisotropy of fiberization in the rolling process. On the other hand, the lower limit of the reduction ratio is preferably 2 or more, and more preferably 3 or more. By setting the lower limit of the reduction ratio in the extrusion molding step within this range, a compact molded product is obtained that is compacted with little air trapped inside, and therefore the product can be easily rolled, and a rolled product with excellent uniformity in thickness and internal composition can be obtained.

[0054] [Rolling process] In this step, the sheet obtained in the above extrusion molding step is rolled.

[0055] The lower limit of the rolling reduction in the rolling step is preferably 0.93, more preferably 0.95, and even more preferably 0.97. By setting the lower limit of the rolling reduction within the above range, the rolling step promotes fiberization of polytetrafluoroethylene and improves elongation, so that a dielectric sheet with good folding resistance can be obtained. In addition, since there is no need to promote fiberization of polytetrafluoroethylene, which requires high pressure, in extrusion molding, extrusion molding at low pressure can be performed. On the other hand, the upper limit of the rolling reduction is preferably 0.99, and even more preferably 0.98. By setting the upper limit of the rolling reduction within the above range, the degree of processing in the rolling step is suppressed, and variations in the properties of thickness and mechanical strength due to excessive processing can be suppressed.

[0056] In the rolling process, it is preferable to roll the sheet by controlling the GAP value between the rolls, rather than by controlling the pressure. The sheet may be rolled from the thickness before the rolling process to the final thickness in one rolling pass, but if the reduction rate in one rolling pass is too large, the thickness of the sheet may vary widely or the sheet may tear. Therefore, it is preferable to roll the sheet to the final thickness in multiple rolling passes.

[0057] In the extrusion and rolling processes, the polytetrafluoroethylene is fibrous and aligned, which may result in anisotropy of the mechanical strength, particularly elongation, of the dielectric sheet. The anisotropy of the mechanical strength may also cause anisotropy of the linear expansion coefficient. In order to suppress this anisotropy, in the rolling process, when rolling is performed multiple times, it is preferable to roll at least once in a direction different from the extrusion direction of the extrusion, preferably in a perpendicular direction.

[0058] The rolling temperature in this step is preferably 30° C. or higher and 100° C. or lower. Uniform rolling can be easily achieved by setting the rolling temperature at 30° C. or higher, which is higher than the transition temperature of polytetrafluoroethylene around room temperature. Uniform rolling can be easily achieved by setting the rolling temperature at 100° C. or lower, at which the degree of vaporization of the auxiliary is small.

[0059] [Auxiliary agent removal process] In this process, the sheet formed in the rolling process is dried to remove the auxiliary agent (liquid lubricant). Drying is a simple and preferable method for removing the auxiliary agent. The drying temperature and time may be appropriately determined according to the properties of the auxiliary agent within a temperature range lower than the melting point of polytetrafluoroethylene.

[0060] According to this method for manufacturing a dielectric sheet, the uniformity of the filler and the uniformity of the thickness as a thin film are ensured, and a dielectric sheet with excellent high frequency characteristics can be easily and reliably manufactured.

[0061] <Method of manufacturing a substrate for a high frequency printed wiring board> The method for manufacturing a substrate for a high-frequency printed wiring board includes the steps of preparing powdered polytetrafluoroethylene and spherical silica, extruding a mixture containing the powdered polytetrafluoroethylene and the spherical silica at a temperature equal to or lower than the melting point of the polytetrafluoroethylene, rolling a sheet body obtained by the extrusion molding step, and laminating a copper foil directly or indirectly on the surface of the dielectric sheet formed after the rolling step. In addition, the mass ratio of silica to polytetrafluoroethylene is 1.3 or more, and the reduction ratio in the extrusion molding is 8 or less. In the method for manufacturing a substrate for a high-frequency printed wiring board, since the mass ratio of silica to polytetrafluoroethylene is 1.3 or more, the linear expansion coefficient of the dielectric sheet can be reduced, and the dimensional stability of the base film against temperature changes can be improved. In addition, by setting the reduction ratio in the extrusion molding to 8 or less, the frictional force between the inner wall of the extruder and the mixture can be reduced, and extrusion molding can be performed at a low pressure. The manufacturing method for a substrate for a high-frequency printed wiring board includes a step of laminating copper foil directly or indirectly onto the surface of a dielectric sheet having excellent high-frequency characteristics, so that a substrate for a high-frequency printed wiring board having excellent high-frequency characteristics can be easily and reliably manufactured.

[0062] The preferred range of the average particle size of the silica is as described above.

[0063] The steps other than the step of laminating the copper foil in the manufacturing method for the high frequency printed wiring board are the same as those in the manufacturing method for the dielectric sheet, and therefore the description will be omitted.

[0064] [Copper foil lamination process] In this step, copper foil is directly or indirectly laminated on the surface of the dielectric sheet formed after the rolling step. As a method for laminating copper foil, for example, a method of thermocompression bonding a dielectric sheet and a copper foil can be mentioned. However, if the dielectric sheet and the copper foil are thermocompression bonded without any treatment, there is a concern that the adhesive strength between them will be low. Therefore, a method of thermocompression bonding after performing a surface treatment such as corona treatment, plasma treatment, or silane coupling treatment on the surface of the dielectric sheet or the copper foil, a method of forming a thin film made of an adhesive composition on the surface of the dielectric sheet or the copper foil, or a method of thermocompression bonding via an adhesive composition by laminating a film formed from the adhesive composition between the dielectric sheet and the copper foil, etc. are preferred. In this way, copper foil may be indirectly laminated on the surface of the dielectric sheet.

[0065] The lower limit of the thermocompression temperature is preferably 320°C, more preferably 330°C. The upper limit of the thermocompression temperature is preferably 390°C, more preferably 380°C. If the thermocompression temperature is below the lower limit, it may be difficult to deform the polytetrafluoroethylene, and good mechanical strength may not be obtained. If the thermocompression temperature exceeds the upper limit, a small amount of corrosive gas may be generated due to decomposition of the polytetrafluoroethylene.

[0066] The pressure of the thermocompression bonding is not particularly limited, and is set to, for example, 4 MPa or more and 30 MPa or less.

[0067] In the manufacturing method of the high frequency printed wiring board substrate, in the step of laminating the copper foil, the copper foil is laminated on the surface of the dielectric sheet via an adhesive layer, and the adhesive layer preferably contains a thermoplastic fluororesin as a main component. In the step of laminating the copper foil, the copper foil is laminated on the surface of the dielectric sheet via an adhesive layer, and the adhesive layer preferably contains a thermoplastic fluororesin as a main component, so that the low roughness copper foil and the dielectric sheet can be firmly bonded while maintaining good high frequency characteristics due to the fluororesin.

[0068] The adhesive layer may be formed by laminating an adhesive layer on the surface of the dielectric sheet before the step of laminating the copper foil, or may be formed by laminating an adhesive layer on the surface of the copper foil.

[0069] From the viewpoint of obtaining good adhesiveness, the thermoplastic fluororesin is preferably a fluororesin having a heat softening temperature of 320° C. or less, and examples thereof include perfluoroalkoxyalkane (PFA) and perfluoroethylenepropene copolymer (FEP).

[0070] The lower limit of the thickness of the adhesive layer is preferably 0.1 μm, more preferably 0.5 μm. The upper limit of the thickness of the adhesive layer is preferably 5.0 μm, more preferably 2.0 μm. By keeping the thickness of the adhesive layer within the above range, the copper foil and the dielectric sheet can be strongly bonded while keeping the linear expansion coefficient of the entire substrate low.

[0071] According to the method for producing a substrate for a high frequency printed wiring board, a substrate for a high frequency printed wiring board having excellent high frequency characteristics can be produced easily and reliably.

[0072] <Dielectric sheet> Fig. 1 is a schematic cross-sectional view of the dielectric sheet. The dielectric sheet 1 contains silica and polytetrafluoroethylene. Since polytetrafluoroethylene has a low dielectric constant, the dielectric sheet 1 is suitable as an insulating base material for a printed wiring board substrate for high-frequency signal processing. The dielectric sheet can be manufactured by the above-mentioned manufacturing method for a dielectric sheet.

[0073] The lower limit of the mass ratio of silica to polytetrafluoroethylene is 1.3, preferably 1.5, and more preferably 1.6. Meanwhile, the upper limit of the mass ratio of silica is preferably 2.0, and more preferably 1.9. By making the mass ratio of silica to polytetrafluoroethylene 1.3 or more, the linear expansion coefficient of the dielectric sheet can be reduced, and the dimensional stability of the dielectric sheet against temperature changes can be improved. Meanwhile, if the mass ratio of silica exceeds the upper limit, the dielectric sheet becomes brittle, and there is a risk of the handleability and folding resistance being reduced.

[0074] The composition of the silica is as described above, and therefore the description thereof will be omitted.

[0075] The upper limit of the elongation anisotropy coefficient is 1.5, and preferably 1.2. The lower limit of the elongation anisotropy coefficient is preferably 1.0. If the elongation anisotropy coefficient is out of the above range, anisotropy occurs in the fiberization and arrangement of polytetrafluoroethylene, and anisotropy occurs in the mechanical strength of the dielectric sheet, which may cause the dielectric sheet to easily tear in a certain direction or cause anisotropy in not only the mechanical strength but also the linear expansion coefficient.

[0076] The lower limit of the minimum tensile elongation of the dielectric sheet is preferably 40% or more, more preferably 80%, even more preferably 100% or more, and even more preferably 150% or more. When the minimum tensile elongation of the dielectric sheet is within the above range, the dielectric sheet has excellent folding resistance despite the high mass ratio of silica. This is because the higher the elongation, the better the folding resistance. Since elongation is mainly caused by the fiberization of polytetrafluoroethylene, it is more affected by the reduction ratio and rolling reduction rate of the extrusion molding in the above manufacturing method than the elastic modulus and breaking strength. To measure the tensile elongation, a sample is used in which the dielectric sheet is sandwiched between a hot press and heated at 350°C for 40 minutes while being compressed in the thickness direction at a pressure of 4 MPa. The measurement method is IPC-TM-650 2.4.19.

[0077] As described above, the silica preferably has an alkyl group having 4 or more carbon atoms on the surface, and more preferably has an alkyl group having 5 or more carbon atoms. On the other hand, the upper limit of the carbon number is preferably 10 or less. When the silica has an alkyl group having 4 or more carbon atoms on the surface, the adhesion between the silica and the polytetrafluoroethylene increases and the elongation improves, so that the dielectric sheet has excellent folding resistance. In addition, the alkyl group is preferably a linear alkyl, and examples of the alkyl group having 4 or more carbon atoms include a butyl group, a pentyl group, a hexyl group, a heptyl group, an octyl group, a nonyl group, and a decyl group.

[0078] The dielectric sheet may contain an inorganic filler other than silica, such as aluminum oxide, magnesium oxide, calcium oxide, talc, barium sulfate, boron nitride, zinc oxide, potassium titanate, glass, titanium oxide, and mica. Inorganic fillers generally have a small linear expansion coefficient, so when an inorganic filler other than silica is blended, the amount of silica blended can be reduced depending on the blending amount. Titanium oxide is preferable as the inorganic filler. By containing an appropriate amount of titanium oxide, the temperature change of the dielectric can be adjusted. From the viewpoint of the processability of the dielectric sheet, the particle size of titanium oxide is preferably 0.1 μm or more and 5.0 μm or less. In addition, as for the blending amount of titanium oxide, from the viewpoint of ease of adjusting the temperature change of the dielectric and imparting a low dielectric constant, the mass ratio to silica is preferably 0.01 to 0.30, more preferably 0.02 to 0.10.

[0079] The dielectric sheet 1 may contain other fluororesins besides polytetrafluoroethylene. In this case, the upper limit of the content of the other fluororesins in the dielectric sheet 1 is preferably 10 mass %, more preferably 5 mass %.

[0080] Furthermore, the dielectric sheet 1 may contain, as optional components, for example, a flame retardant, a flame retardant assistant, a pigment, an antioxidant, a reflector, a masking agent, a lubricant, a processing stabilizer, a plasticizer, a foaming agent, etc. In this case, the upper limit of the content of the optional components in the dielectric sheet 1 is preferably 25% by mass, and more preferably 10% by mass.

[0081] As the flame retardant, various known flame retardants can be used, for example, halogen-based flame retardants such as bromine-based flame retardants and chlorine-based flame retardants.

[0082] As the above-mentioned flame retardant auxiliary, various known ones can be used, for example, antimony trioxide.

[0083] As the pigment, various known pigments can be used, for example, titanium oxide.

[0084] As the antioxidant, various known antioxidants can be used, for example, phenol-based antioxidants.

[0085] As the reflecting agent, various known materials can be used, for example, titanium oxide.

[0086] The dielectric sheet preferably has, in a longitudinal section in the thickness direction, a lamellar first phase mainly composed of polytetrafluoroethylene and a lamellar second phase mainly composed of silica. By having the lamellar first phase and the lamellar second phase, the respective characteristics of polytetrafluoroethylene and silica, for example, the characteristics of high elongation and high strength due to the fiberization of polytetrafluoroethylene, can be more easily exhibited.

[0087] The thickness of the first phase is preferably 0.1 μm or more and 10.0 μm or less, more preferably 0.1 μm or more and 5.0 μm or less, and even more preferably 0.1 μm or more and 3.0 μm or less. If the thickness of the first phase layer is too small, it is difficult to exhibit the characteristics of high elongation and high strength due to the fiberization of polytetrafluoroethylene, and if it is too large, it is difficult to reduce the linear expansion coefficient, and as a result of high-density aggregation of silica, the portion becomes brittle, causing a problem of reduced elongation of the dielectric sheet. The thickness of the first phase layer can be adjusted by the particle size of polytetrafluoroethylene, the particle size of silica, the stirring state of polytetrafluoroethylene and silica, and the extrusion molding and rolling conditions.

[0088] Specifically, the first phase and the second layer are observed when a cross-sectional sample of the dielectric sheet is prepared by a cross-section polisher method and observed with a scanning electron microscope at a magnification of 3000 times over a length of 42 μm in the in-plane direction and a length of 30 μm in the thickness direction. FIG. 2 shows an image of a longitudinal section of the dielectric sheet in the thickness direction taken with the scanning electron microscope. The dielectric sheet shown in FIG. 2 was produced under the conditions of an average particle size of polytetrafluoroethylene of 500 μm, an average particle size of silica of 0.5 μm, a mass ratio of silica to polytetrafluoroethylene of 1.9, a reduction ratio in extrusion molding of 4.4, and a rolling reduction rate of 0.98 in the rolling process. The dark linear layer is the first phase 11 mainly composed of polytetrafluoroethylene. The region mainly composed of spherical silica is the second phase 12.

[0089] The dielectric sheet preferably has a uniform distribution of silica in a longitudinal section in the thickness direction. The ratio of the sum of the cross-sectional areas of silica within 10 μm from the back surface of the dielectric sheet in the longitudinal section to the sum of the cross-sectional areas of silica within 10 μm from the front surface of the dielectric sheet in the longitudinal section is preferably 1.00 to 1.20, more preferably 1.00 to 1.10, and even more preferably 1.00 to 1.05. If the ratio of the sum of the cross-sectional areas of silica falls outside the above range, the high-frequency characteristics of the electric circuit provided on the front surface of the dielectric sheet and the electric circuit provided on the back surface of the dielectric sheet will differ, making it difficult to design the electric circuit and the electric component. In measuring the ratio of the sum of the cross-sectional areas of silica, the length of the line corresponding to the front surface of the dielectric sheet and the length of the line corresponding to the back surface of the dielectric sheet are both 500 μm.

[0090] The lower limit of the average thickness of the dielectric sheet 1 is preferably 30 μm, more preferably 50 μm, and even more preferably 100 μm. On the other hand, the upper limit of the average thickness of the dielectric sheet 1 is preferably 1000 μm, more preferably 500 μm, and even more preferably 300 μm. If the average thickness is less than the lower limit, the mechanical strength may be insufficient. In addition, the effect of dimensional errors on the high-frequency characteristics of the electric circuit may become large, which may make it difficult to design the circuit and manufacture the circuit components. On the other hand, if the average thickness exceeds the upper limit, the thickness of the substrate for high-frequency printed wiring boards may become too large, and when flexibility is required for the dielectric sheet 1, the flexibility may be insufficient. Here, the "average thickness" refers to the distance between the average line of the interface on the front side and the average line of the interface on the back side within the measurement length in a cross section cut in the thickness direction of the object. The "average line" refers to a virtual line drawn along the interface, such that the total area of ​​the peaks (total area above the virtual line) and the total area of ​​the valleys (total area below the virtual line) defined by the interface and this virtual line are equal. The upper limit of the difference between the maximum and minimum thicknesses of the dielectric sheet is 1 m of the dielectric sheet. 2 In this case, the difference is preferably ±10 μm or less, more preferably ±5 μm or less, and even more preferably ±2 μm or less, because if the upper limit of the difference is outside the above range, it may become difficult to design the circuit and manufacture the circuit components.

[0091] The dielectric sheet has excellent high-frequency characteristics and folding resistance, and is suitable for use as a base film for high-frequency printed wiring boards.

[0092] <High frequency printed wiring board substrate> Fig. 3 is a schematic cross-sectional view of the substrate for high-frequency printed wiring board. As shown in Fig. 3, the substrate for high-frequency printed wiring board 3 includes the dielectric sheet 1 and a copper foil 2 laminated directly or indirectly on the surface of the dielectric sheet 1. That is, the substrate for high-frequency printed wiring board 3 includes a copper clad laminate (CCL). As such, the substrate for high-frequency printed wiring board 3 includes the dielectric sheet 1, and thus the substrate for high-frequency printed wiring board has excellent high-frequency characteristics and folding resistance.

[0093] The details of the configuration of the dielectric sheet are as described above.

[0094] [copper foil] The copper foil 2 is etched or otherwise processed to form a conductor pattern of a high-frequency printed wiring board.

[0095] The copper foil 2 is used as a conductive layer, and is processed into various patterns by, for example, etching, when a printed wiring board is manufactured.

[0096] The copper foil 2 is not particularly limited as long as it is applicable to a printed wiring board, and may be appropriately selected according to the required characteristics. The lower limit of the purity of copper in the copper foil 2 is preferably 99.5% by mass, more preferably 99.8% by mass. The upper limit of the purity is preferably 99.999% by mass. By setting the purity to be equal to or higher than the lower limit, the resistance of the copper foil 2 can be reduced, so that the transmission loss can be further suppressed. On the other hand, if the purity exceeds the upper limit, there is a risk of an increase in costs. In addition, it is preferable that the surface of the copper foil is subjected to a treatment generally performed as a surface treatment of copper foil for printed wiring boards, that is, a treatment for rust prevention or a treatment for improving adhesion. Such treatment is performed by forming a layer made of Zn, Ni, Cr, Si, etc. on the surface layer of the copper foil.

[0097] The lower limit of the average thickness of the copper foil 2 is preferably 5 μm, more preferably 10 μm. On the other hand, the upper limit of the average thickness is preferably 100 μm, more preferably 75 μm. A thick copper foil has the advantage of a large current capacity and good thermal conductivity. However, if the demand for multi-layering and thinning of high-frequency printed wiring boards is emphasized, the upper limit of the average thickness is preferably 20 μm, more preferably 15 μm.

[0098] The upper limit of the maximum height roughness Rz of the surface of the copper foil on the dielectric sheet side is preferably 2 μm, more preferably 1 μm. When the maximum height roughness Rz of the surface on the dielectric sheet side is within the above range, the unevenness of the portion where the high frequency signal is concentrated due to the skin effect is reduced, and the current is more likely to flow linearly, so that the transmission loss can be further suppressed. Therefore, the high frequency characteristics of the substrate for high frequency printed wiring boards can be further improved.

[0099] The substrate 3 for a high-frequency printed wiring board may include layers other than the dielectric sheet 1 and the copper foil 2.

[0100] The copper foil 2 of the substrate 3 for high-frequency printed wiring board may be laminated via an intermediate layer such as a known adhesive layer on at least one surface of the dielectric sheet 1. For example, the adhesive layer is laminated on the dielectric sheet to bond the copper foil 2 to the dielectric sheet 1.

[0101] The substrate for high-frequency printed wiring boards has the dielectric sheet, and therefore has excellent high-frequency characteristics and folding resistance. The substrate for high-frequency printed wiring boards 3 can be used, for example, as a substrate for printed wiring boards for a subtractive method. When the substrate for high-frequency printed wiring boards 3 is applied to the subtractive method, the copper foil 2 is masked with a resist pattern or the like and etched, whereby the copper foil 2 is patterned to form copper wiring or the like. The substrate for high-frequency printed wiring boards is suitably used for communication devices using high frequencies, etc.

[0102] [Other embodiments] The embodiments disclosed herein should be considered to be illustrative and not restrictive in all respects. The scope of the present disclosure is not limited to the configurations of the above-described embodiments, but is indicated by the scope of the claims, and is intended to include all modifications within the meaning and scope equivalent to the scope of the claims.

[0103] The high-frequency printed wiring board substrate may have copper foil laminated on one side of the dielectric sheet as in the above embodiment, or may have copper foil laminated on both sides of the dielectric sheet.

[0104] The substrate for high frequency printed wiring boards does not necessarily have to be used as a substrate for a flexible printed wiring board, but may be used as a substrate for a rigid printed wiring board. EXAMPLES

[0105] The present disclosure will be specifically described below based on examples, but the present disclosure is not limited to these examples.

[0106] [Dielectric sheets No. 1 to No. 16 (Test examples No. 1 to No. 16)] (1) Mixing the materials Polytetrafluoroethylene with an average particle size of 500 μm, silica with an average particle size as shown in Table 1, titanium oxide with an average particle size of 0.2 μm, and naphtha as an auxiliary agent were placed in a container in the amounts as shown in Table 1. The amount of naphtha was equivalent to 17% by mass of the total of the other materials. The container was rotated at 5 rpm for 100 minutes at 10°C to mix the materials. In No. 15, silica with a vinyl group on the surface by silane coupling treatment was used, and in No. 16, silica with a hexyl group on the surface by silane coupling treatment was used. In the other samples, no surface treatment was performed. The hydrophobicity of the silica with a vinyl group on the surface was 0.08, and the hydrophobicity of the silica with a hexyl group on the surface was 0.10.

[0107] (2) Extrusion molding process Next, the mixture obtained in the material mixing process was extrusion molded using a die. The temperature of the extrusion mold was 45°C. The molding pressure was measured using a capillary rheometer (Toyo Seiki CAPIROGRAPH 1C), which can be considered a small extrusion molding device, because normal equipment cannot measure high pressures. The molding pressure is shown in Table 1. The extrusion molding temperature was 60°C. The reduction ratio was adjusted by changing the hole diameter of the capillary. The diameter of the capillary gradually decreases from the thick part connected to the cylinder to the hole at the tip, and in a cross-sectional view including the symmetrical axis of the capillary, the angle between the two lines corresponding to the inner wall of the capillary is 90 degrees.

[0108] (3) Rolling process A 4 mm thick extrusion molded product was sandwiched between two carrier films (125 μm thick polyethylene terephthalate (PET)) and passed between two rolling rolls with a diameter of 200 mm and a width of 300 mm. Then, the product was rolled to a thickness of 125 μm to obtain a dielectric sheet. The rolling roll temperature was 55° C. The rolling speed was 1 m / min. The rolling direction was the extrusion direction of the extrusion molded product and the width direction perpendicular to the extrusion direction, and the elongation anisotropy coefficient was adjusted. Specifically, about 90% of the rolling from 4 mm to 125 μm was performed in the width direction. Next, the dielectric sheet was peeled off from the carrier film and dried at 100° C. for two days. Then, the No. 1 to No. 11 dielectric sheets were sandwiched between a hot press and heated at 350° C. for 40 minutes while being compressed in the thickness direction at a pressure of 4 MPa.

[0109] [evaluation] The above dielectric sheets No. 1 to No. 11 were subjected to the following evaluations.

[0110] (Linear expansion coefficient) The term "linear expansion coefficient" refers to the linear expansion rate measured in accordance with the dynamic mechanical property testing method described in JIS-K7244-4 (1999).

[0111] First, the dielectric sheets No. 1 to No. 11 were cut out and measured using a TMA (Hitachi High-Tech Science SS7100) under the conditions of a sample length of 10 mm and a tensile load of 5 gf. After heating from -30°C to 200°C at a rate of 5°C / min, the linear expansion coefficient was calculated from the dimensional change from 120°C to 20°C when cooling at the same rate, and evaluated in three stages. In Table 1, if this value is 40 ppm / °C or more, the dimensional change is deemed large and is judged as C (poor), if it is 30 ppm / °C or more but less than 40 ppm / °C, it is judged as B (Fair), and if it is less than 30 ppm / °C, it is judged as A (Good).

[0112] (Tensile elongation) In accordance with IPC-TM-650 2.4.19, measurements were carried out at 25° C. using an autograph (AGS-X manufactured by Shimadzu Corporation), and the maximum tensile elongation, minimum tensile elongation and elongation anisotropy coefficient were determined.

[0113] (Molding pressure) Based on the results of the molding pressure, the extrusion performance was evaluated according to the following three-level criteria: A is good, B is fair, and C is poor.

[0114] A: Less than 70MPa B: 70MPa or more and less than 90MPa C: Molding pressure is 90MPa or more When the molding pressure was 90 MPa or higher, the material was not extruded using a normal extrusion molding device, and furthermore, excessive fiberization in the extrusion molding direction occurred, making it difficult to obtain a dielectric sheet with a small elongation anisotropy coefficient, and therefore the material was rated as C.

[0115] (Extrusion appearance) The appearance after extrusion was evaluated according to the following three-level scale: A is good, B and B' are fair, and C is poor.

[0116] A: No problems with appearance, good condition B: There are slight traces of waviness in the center. B´: Slight clogging of the edge is observed C: Poor appearance

[0117] (Hydrophobicity) Silica was heated in a vacuum at 100°C using a Belprep vac-II manufactured by Microtrap Bell Co., Ltd., and the adsorption isotherm was measured using the nitrogen gas adsorption method at liquid nitrogen temperature, and the BET specific surface area by nitrogen adsorption was calculated using the BET method. Similarly, silica was heated in a vacuum at 100°C using a Belprep vac-II manufactured by Microtrap Bell Co., Ltd., and the adsorption isotherm was measured at 25°C, and the BET specific surface area by water vapor adsorption was calculated using the BET method. The hydrophobicity was calculated by dividing the value of the BET specific surface area by water vapor adsorption by the value of the BET specific surface area by nitrogen adsorption. The lower this value, the more hydrophobic it is.

[0118] The evaluation results of the dielectric sheets No. 1 to No. 16 are shown in Table 1. Note that "-" indicates that the corresponding component was not contained.

[0119] [Table 1]

[0120] From the results in Table 1, good results were obtained in terms of linear expansion coefficient and molding pressure in test examples 3, 5 to 8, 15, and 16 in which the mass ratio of the silica to polytetrafluoroethylene was 1.3 or more, the average particle size of the silica was 0.1 μm or more and 3.0 μm or less, and the reduction ratio was 8 or less, and in test examples 12 to 14 in which the mass ratio of the silica to polytetrafluoroethylene was 1.3 or more, a first silica having an average particle size of 0.1 μm or more and 0.9 μm or less and a second silica having an average particle size of 4 μm or more and 9 μm or less, the mass ratio of the first silica to the polytetrafluoroethylene was 0.2 or more and 1.9 or less, and the reduction ratio was 8 or less.

[0121] On the other hand, the linear expansion coefficient was high in Test Example No. 1, which did not contain silica, and Test Example 2, in which the mass ratio of silica to polytetrafluoroethylene was less than 1.3. Furthermore, the molding pressure was high in Test Example No. 4, in which the reduction ratio exceeded 8, and Test Examples No. 9, 10, and 11, in which the average particle size of silica exceeded 3 μm.

[0122] In addition, comparing Test Example No. 15, which was treated with vinyl groups as a surface treatment, Test Example No. 16, which was treated with hexyl groups, and Untreated Test Example No. 8, Test Example No. 16, which was treated with hexyl groups, had a greater improvement in minimum tensile elongation than Test Example No. 15, which was treated with vinyl groups with a higher degree of hydrophobicity. This shows that the folding endurance is improved more effectively by increasing the adhesion between the silica and polytetrafluoroethylene by having the silica have alkyl groups with 4 or more carbon atoms on the surface, rather than by increasing the hydrophobicity of the silica surface.

[0123] The above results demonstrate that the dielectric sheet manufacturing method can reliably manufacture dielectric sheets with excellent high frequency characteristics by extrusion molding under low pressure. [Explanation of symbols]

[0124] 1 Dielectric sheet 2 Copper foil 3. High-frequency printed wiring board substrate 11 Phase 1 12 Phase 2

Claims

1. extruding a mixture containing powdered polytetrafluoroethylene and spherical silica at a temperature equal to or lower than the melting point of the polytetrafluoroethylene; a step of rolling the sheet body obtained by the extrusion molding step; It is equipped with a mass ratio of the silica to the polytetrafluoroethylene is 1.380 or greater and 1.750 or less; The silica has an average particle size of 0.1 μm or more and 3.0 μm or less, The method for producing a dielectric sheet, wherein the reduction ratio in the extrusion molding is 8 or less.

2. extruding a mixture containing powdered polytetrafluoroethylene and spherical silica at a temperature equal to or lower than the melting point of the polytetrafluoroethylene; a step of rolling the sheet body obtained by the extrusion molding step; It is equipped with a mass ratio of the silica to the polytetrafluoroethylene is 1.380 or greater and 1.750 or less; The silica includes a first silica having an average particle size of 0.1 μm or more and 0.9 μm or less and a second silica having an average particle size of 4.0 μm or more and 9.0 μm or less, a mass ratio of the first silica to the polytetrafluoroethylene is 0.2 or more and 1.9 or less; The method for producing a dielectric sheet, wherein the reduction ratio in the extrusion molding is 8 or less.

3. 3. The method for producing a dielectric sheet according to claim 1, wherein the rolling step has a rolling reduction of 0.93 or more.

4. A step of producing a dielectric sheet by the method according to any one of claims 1 to 3; laminating copper foil directly or indirectly on a surface of the dielectric sheet; A method for manufacturing a substrate for a high-frequency printed wiring board comprising:

5. In the step of laminating the copper foil, the copper foil is laminated on the surface of the dielectric sheet via an adhesive layer, 5. The method for producing a substrate for a high frequency printed wiring board according to claim 4, wherein the adhesive layer is mainly composed of a thermoplastic fluororesin.

6. Contains silica and polytetrafluoroethylene, a mass ratio of the silica to the polytetrafluoroethylene is 1.380 or greater and 1.750 or less; The ratio of the maximum tensile elongation to the minimum tensile elongation is 1.5 or less, and the minimum tensile elongation is 40% or more, A dielectric sheet comprising silica having an average particle size of 0.3 μm or more and 1.0 μm or less, or a mixture of large-diameter silica having an average particle size of 4.0 μm or more and 9.0 μm or less and small-diameter silica having an average particle size of 0.1 μm or more and 0.9 μm or less.

7. 7. The dielectric sheet according to claim 6, wherein in a longitudinal section in the thickness direction of the sheet, there is a layered first phase mainly composed of said polytetrafluoroethylene, and a layered second phase mainly composed of said silica.

8. 8. The dielectric sheet according to claim 7, wherein the first phase has a thickness of 0.1 μm or more and 10.0 μm or less.

9. 9. The dielectric sheet according to claim 6, wherein the silica has an alkyl group having 4 to 10 carbon atoms on a surface thereof.

10. A dielectric sheet according to any one of claims 6 to 9, A copper foil is laminated directly or indirectly on the surface of the dielectric sheet. A substrate for a high frequency printed wiring board comprising:

11. 11. The substrate for a high frequency printed wiring board according to claim 10, wherein the maximum height roughness Rz of the surface of the copper foil on the side of the dielectric sheet is 2 [mu]m or less.

12. 12. The substrate for high frequency printed wiring board according to claim 10, wherein the copper foil is laminated on the surface of the dielectric sheet via an adhesive layer mainly composed of a fluororesin.

Citation Information

Patent Citations

  • Polytetrafluoroethylene sheet or film, gasket tape obtained therefrom, and method for manufacturing them

    JP2003025423A

  • Flexible printed wiring board

    JP2008235346A

  • Polytetrafluoroethylene porous membrane with small elongation anisotropy and process for production thereof

    JP2012001591A

  • Fluororesin composition

    JP2015209480A

  • Tabular composite material containing polytetrafluoroethylene and filler

    WO2018221556A1